SISTEM NEGARA KHILAFAH DALAM TINJAUAN HUKUM ISLAM: KONTROVERSI ATAS WACANA SISTEM KHILAFAH DALAM KONTEKS INDONESIA - Ahmad, Nehru Millat (Al-Iqro', 2024)
The Islamic State or al-Islamiyah khilafah is a system of government based on Islamic sharia. In such a system, Islamic law is the primary foundation for regulating all matters, such as laws, state finances, relations with peoples and relations with other countries, as described in the fiqh siyasah. (hukum perpolitikan). This study wants to examine the connection of the khilafah system in a State, and whether such a system can be enforced in the State of Indonesia whose notes have been guided by the Pancasila and UUD 1945. This research is categorized as qualitative research, meaning exposure and description of problems according to research factors. A library study is a method of research that emphasizes a library as an object of study. The study finds that Islam does not provide clear and detailed rules on how the system of government of a country is formed, be it a republic, a caliphate, a priest, a monarch, an authoritarian, or a democracy. Islam emphasizes that a system can produce and bring a country into an atmosphere of justice, prosperity, and justice, free from the tyranny of the majority against the minority.